Menemukan Makna Pembenaran Di Dalam Perumpamaan Yesus Menurut Lukas 18:9-14 - Adi Haryono Sianturi (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2023)
The teachings of Jesus in the Gospels contain very many parables. These parables remain relevant in the context of today's life which is very complex in its aspects of life. Apart from that, the reading of parables is often read in an allegorical style that has been passed down by the church fathers and has been going on for a very long time. The church should have a new way of reading parable texts to get a more contextual meaning of the text today. This article tries to present an existentialist approach to reading the parables of Jesus, namely one of reading parable texts by understanding these parables as pure parables of that era. The writer argues that by reading Luke 18: 9-14 with an existentialist approach, the meaning of justification intended by Jesus in the text will be found clearly.